2011
DOI: 10.1007/s11250-011-9901-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pathology of dermatophilosis in camels (Camelus dromedaries) in Iran

Abstract: Gross and histopathologic lesions of the integumentary system were studied in 103 camels (Camelus dromedarius) slaughtered in Yazd Province of Iran. Dermatophilosis was diagnosed in 14 (13.6%) of the studied camels. Grossly, patchy thickening of the skin with dark brown scabs or crusts were observed on the rump, flanks, abdomen, shoulders, and neck. A heavy infestation with brown hard ticks was present on the lesions in almost all of the affected camels. On parasitology examination, all the ticks were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
1
3
1
Order By: Relevance
“…This variation is due to the result of the wide use of ox tetracycline drugs among camel herds and also may be from different climates according to the duration of the study. Macroscopically and microscopically characterization for Dermatophilus congolensis in this study was in full agreement with other results discovered others researchers [16,17,18] . The study revealed higher significant different effect of sex on prevalence of Dermatophillosis; the incidence rate was more infected in males than females.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This variation is due to the result of the wide use of ox tetracycline drugs among camel herds and also may be from different climates according to the duration of the study. Macroscopically and microscopically characterization for Dermatophilus congolensis in this study was in full agreement with other results discovered others researchers [16,17,18] . The study revealed higher significant different effect of sex on prevalence of Dermatophillosis; the incidence rate was more infected in males than females.…”
Section: Discussionsupporting
confidence: 93%
“…D. congolensis was first described in domestic cattle in Zaire, Africa in 1910 [15] This present study recorded 3% of camels provided to Tamboul livestock markets from all over Sudan from 2015 to 2016 were infected with Dermatophillosis. The prevalence rate in this study was less than the results recorded by Gitao et al, [16] that revealed 20% of camels in the Butana area were infected with Dermatophillosis [17] . The prevalence of camel Dermatophillosis in Iran was 13.6%.…”
Section: Discussioncontrasting
confidence: 83%
“…Dermatophilus congolensis causes exudative dermatitis in multiple species and is typically associated with tick and biting fly-transmission, although it can also be spread by contact [ 156 , 157 , 158 , 159 ]. Prevalence levels were similar in Kenya to Sudan and Iran, at between 12 and 30%, and were significantly higher during the wet season [ 53 , 160 , 161 ]. This may indicate an increased risk as camel production moves into areas with higher rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…The condition has been described in a wide range of animal hosts and humans [3,4]. The most affected domestic animals are cattle [5], camels [6,7], horses [8], sheep [9], goats [10], occasionally cats [11], and other species [4]. In camels, a mixed infection of D. congolensis and Microsporum gypseum has been reported [12].…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged wetting of skin during or after the rainy season may predispose camels to more severe infection because of the emulsification of the wax barrier and disruption of the stratum cornium. Human infection, in the form of pustules, furuncles, or desquamative eczema of the hands or forearms or superficial erosions of the esophagus, can be acquired through contact with diseased animals [7,15]. Camel dermatophilosis has been reported in Kenya, Sudan and Saudi Arabia [16], United Arab Emirates [17], Egypt [18], Ethiopia [19], Iran [20], India [21], and Belgium [5].…”
Section: Introductionmentioning
confidence: 99%